Students’ Performance in Speaking Skill and Self-Efficacy : An Correlational Study - Khusnul Khotimah; Rengganis Siwi Amumpuni; Samsul Arifin (Jurnal Paedagogy, 2023)
The objective of this study is to investigate the extent to which students' levels of self-efficacy are correlated with their levels of success in speaking skill assessments of the students of MAN 1 Madiun. The research method used quantitative research. The population in this study are all the eleventh grade students. The sample for this study are students from class XI MIA 2 consists of 22 students. The researcher uses using purposive sampling technique. The researcher uses questionnaires to students to determine the level of students’ self-efficacy and uses speaking test. Pearson Product Moment (r) formula using t-test is used in this research. The results show that the highest score is 95. Meanwhile, the lowest score is 82. The result of the Pearson product moment correlation is.052 with a negative sign. The conclusion that can be drawn from these findings is that there is a negative correlation  between speaking ability and self-efficacy, as well as the results of significance levels above 0.05.This is what causes scores on students to be lacking. Besides self-efficacy, it has a very positive effect on each student. The implication of this research is to describe the correlation between students’ self-efficacy and their performance in speaking skill so the teacher and other researchers can get information related with that.